Biology of Amitus fuscipennis (Mac Grown & Nebeker) under three ecological conditions in Rionegro (Ant.) - MEDINA, PIEDAD SACRAMENTO; SALDARRIAGA-V., ALFREDO; PÉREZ-G., LUZ ELENA (Revista Colombiana de Entomología, 1994)
Due to the economic importance of the greenhouse whitefly in Colombia and specifically in the eastern part of Antioquia, on ornamentals, and horticultural crops, it has been necessary to look for other alternatives of control different to the usage of insecticides. Because of the natural presence ofAmitusfuscipennis, a parasitoid of the immature stages of the whitefly and its potential utilization in programs of integrated management of this pest, a basic study of its biology was carried out under three ecological conditions and two host plants. The cycle life evaluation had as a base on the effective parasitism of A. fuscipennis on the first instar of the T. vaporariorum. The duration from egg to the emergence of the adult on chrysanthemum under laboratory (T=19.14°C; R.H.= 81.96%), greenhouse (T= 19.54°C; R.H.= 81.64%) and field conditions (T= 17.96°C; H.R.= 81.82%) was 44.57; 46.4 and 66.5 days; on beans the duration was 35.93; 42.43 and 53.7 days, respectively. Under the three ecological conditions, there was a highly significant difference in the development of the parasitoid in the two host plants. In the laboratory, the female of A. fuscipennis laid an average of 103.55 eggs in 13.83 days. The adult life span was evaluated in the laboratory with an average of 11 days when fed with a honey bee solution of 20%, the relative humidity of 80.13%, and a temperature of 18.5°C. Under greenhouse conditions, the female of the parasitoid was able to the parasite, without a statistical difference, the three first instars of T. vaporariorum. Through the dissection of immature parasite stages, the morphological description of the different stages of A. fuscipennis was made.